Mongolian spots: How important are they? - Gupta, Divya (Baishideng Publishing Group Co., Limited, 2013)
Mongolian spots (MS) are congenital birthmarks seen most commonly over the lumbosacral area. They are bluish-green to black in color and oval to irregular in shape. They are most commonly found in individuals of African or Asian ethnic background. Although these lesions resolve by one to two years of age, widespread, extrasacral and dark colored MS sometimes persist into adulthood. Aberrant MS over occiput, temple, mandibular area, shoulders and limbs may be confused with other dermal melanocytoses and bruises secondary to child abuse, thus necessitating documentation at birth. Although traditionally believed to be benign in nature, they have now been shown to co-exist with inborn errors of metabolism, most commonly GM1 gangliosidosis and mucopolysaccharidosis type I (Hurler’s disease), followed by mucopolysaccharidosis type II (Hunter’s syndrome), mucolipidosis, Niemann-Pick disease and mannosidosis. They have also been seen to co-exist with various vascular or other pigmented birthmarks like café-au-lait macules. Co-existing Mongolian spots and vascular birthmarks like nevus flammeus, nevus anemicus or nevus spilus is termed as phakomatosis pigmentovascularis. This review focuses on the important associations of Mongolian spots and stresses upon the importance of screening babies with extensive MS.